2015
DOI: 10.1161/circheartfailure.114.001677
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Treatment of Mice With Pressure-Overload–Induced Heart Failure Improves Diastolic Function and Cardiac Energy Metabolism

Abstract: Background— Although resveratrol has multiple beneficial cardiovascular effects, whether resveratrol can be used for the treatment and management of heart failure (HF) remains unclear. In the current study, we determined whether resveratrol treatment of mice with established HF could lessen the detrimental phenotype associated with pressure-overload–induced HF and identified physiological and molecular mechanisms contributing to this. Methods and Results— … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 53 publications
7
93
0
Order By: Relevance
“…A large body of evidence has shown that Res may help to prevent the development of certain cancers and cardiovascular diseases due to antiviral, antioxidant and anti-inflammatory actions. A recent study showed that Res may attenuate left ventricular hypertrophy via inhibiting NFAT-dependent transcription and suppress heart failure and reverse myocardial remodeling [21,22]. Res treatment may inhibit high blood pressure and attenuate apoptosis of ventricular myocytes and improve ventricular function [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence has shown that Res may help to prevent the development of certain cancers and cardiovascular diseases due to antiviral, antioxidant and anti-inflammatory actions. A recent study showed that Res may attenuate left ventricular hypertrophy via inhibiting NFAT-dependent transcription and suppress heart failure and reverse myocardial remodeling [21,22]. Res treatment may inhibit high blood pressure and attenuate apoptosis of ventricular myocytes and improve ventricular function [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…To the extent that we are approaching an asymptote with addressing neurohormonal activation, these systems are fertile targets, especially if imaging tools such as MRI or positron emission tomography can be used to identify those patient subsets with the most marked changes for early study of targeted therapeutics. 26,27 Disrupting the Successful Stack of Therapies Once the benefit of ACEi was demonstrated in the Studies of Left Ventricular Dysfunction (SOLVD) trial, additional agents have each been stacked on top of previous standard evidencebased therapy. Orthogonal to the stack has been the principle that assessment and correction of fluid retention is a crucial adjunct to all therapies for HF.…”
Section: Potential Approaches To Individualization Of Therapy For Hfrefmentioning
confidence: 99%
“…A large body of evidence has shown that Resveratrol has antiviral, antioxidant and anti-inflammatory actions, and may help prevent the development of certain cancers and cardiovascular diseases [19,22]. Resveratrol at a dosage of 146 mg/kg/day in rats may attenuate pathology left ventricular hypertrophy via inhibiting NFAT-dependent transcription [17].…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol at a dosage of 146 mg/kg/day in rats may attenuate pathology left ventricular hypertrophy via inhibiting NFAT-dependent transcription [17]. Resveratrol treatment (~320mg/kg/day) also may suppress transverse aortic constriction (TAC)-induced heart failure and reverse myocardial remodeling by restored cardiac AMP-activated protein kinase (AMPK) activation in mice [22]. Resveratrol treatment (~320mg/kg/day in mice) may inhibit high blood pressure (BP) and prevent myocardial hypertrophy through mediating LKB1-AMPK-eNOS signaling axis [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation